ANALISIS PENERAPAN AKUNTANSI LINGKUNGAN PADA BADAN RUMAH SAKIT UMUM DAERAH (BRSUD) TABANAN - Ni Made Indrawati; I Gusti Ayu Intan Saputra Rini (KRISNA: Kumpulan Riset Akuntansi, 2018)
Abstract This research entitled "Analysis of Application of Environmental Accounting at Badan Umum Umum Daerah (BRSUD) Tabanan". This study aims to determine the application of environmental accounting at the Regional General Hospital Board (BRSUD) Tabanan as an effort to reduce the environmental impact caused by hospital operational activities and to know the reporting of environmental costs in the financial statements of the hospital. This research is qualitative descriptive research. The variables used in this research are environmental activity and environmental cost treatment. The result of this research is environmental activity done by Badan Badan Umum Umum Daerah (BRSUD) Tabanan that is solid and liquid waste processing by using incinerator and WWTP. Badan General Hospital District (BRSUD) Tabanan not yet apply environmental accounting perfectly according to existing theory. The Tabanan Regional Hospital Board (BRSUD) identifies the environmental costs as direct expenditure and indirect expenditure, recognizes the environmental costs when it has benefited from it even though cash has not yet been issued, the measurement of environmental costs with rupiah monetary units referring to the realization of the previous period costs by the amount of costs incurred, presenting and disclosing the overall environmental costs in the financial statements together with similar costs such as service fees and general and administrative costs. The cost of environmental quality issued by the Regional General Hospital Board (BRSUD) Tabanan amounted to 28.21% of operational cost and budget management has reached 76.62%. Keywords: Environmental accounting, environmental activities, and environmental costs